FORMING CREATIVITY IN CHILDREN THROUGH FOLK INSTRUMENTS - Fazilov Q. (Galaxy International Interdisciplinary Research Journal, 2024)
This article talks about improving the technologies of forming children’s musical creativity with the help of Uzbek folk instruments.